Stereospecific Synthesis of Alkenes by Eliminative Cross‐Coupling of Enantioenriched sp3‐Hybridized Carbenoids. (1st September 2016) - Wu, Zhenhua; Sun, Xun; Potter, Kristin; Cao, Yang; Zakharov, Lev N.; Blakemore, Paul R.
Abstract: 1‐Aryl‐1, 2‐dialkylethenes were generated by a sequence of electrophilic substitution, 1, 2‐metalate rearrangement, and β‐elimination initiated by the addition of enantioenriched α‐(carbamoyloxy)alkylboronates to enantioenriched lithiated carbamates. The carbenoid stereochemical pairing [i.e., " like "=( S )+( S ) or " unlike "=( S )+( R )] and the elimination mechanism ( syn or anti ), not substituent effects, determined the configuration of the trisubstituted alkene target. For example, ( Z )‐2, 5‐diphenyl‐2‐pentene was produced in 70 % yield with E / Z =5:95 by a like combination of Li and B carbenoids and syn (thermal) elimination whereas the E isomer was obtained in the same yield with E / Z >98:2 by an otherwise identical process involving an unlike stereochemical pairing. The concept elaborated overcomes an intrinsic limitation of traditional strategies for direct connective alkene synthesis, which cannot realize meaningful stereochemical bias unless the alkene substituents are strongly differentiated.